Semantyka znaków w adaptacjach filmowych Miasteczka Salem Stephena Kinga - Rawski, Jakub (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article attempts to analyze the film adaptations of Stephen King’s ‘Salem’s Lot directed by Tobe Hooper (1979) and Mikael Salomon (2004) from the perspective of the semiotics of popular culture, with particular emphasis on character creation and the components of the space of the depicted world. The semiotic approach used in the analysis is based on recognizing the primacy of intentions generated by the work and decoded by the recipient, and not reading the intentions of the sender. At the center of the discussion are film signs and an attempt to read the meanings they create. Semiotic analysis makes it possible to demonstrate that various elements related to the creation of characters and the poetics of space carry senses and meanings immanently inscribed in the plot fabric of the text. Film adaptations of one of King’s most famous novels, and especially Hooper’s film, are far from postmodern games with the recipient. In the two films discussed here, the elements of the semiosphere are clear, which, as specific signs of the film narrative, create semiological chains. It is also important to indicate how these adaptations fit into the cultural tradition of the vampire theme and to what extent new approaches have been introduced in relation to the literary original.